Circulating estradiol and its biologically active metabolites in endometriosis and in relation to pain symptoms - Emond, Jean-Philippe; Caron, Patrick; Pušić, Maja; Turcotte, Véronique; Simonyan, David; Vogler, Andrej; Osredkar, Joško; Rižner, Tea Lanišnik; Guillemette, Chantal (Frontiers in Endocrinology, 2023)
Objectives: Endometriosis (EM) is an estrogen-dominant inflammatory disease linked to infertility that affects women of reproductive age. EM lesions respond to hormonal signals that regulate uterine tissue growth and trigger inflammation and pain. The objective of this study was to evaluate whether estradiol (E2) and its biologically active metabolites are differentially associated with EM given their estrogenic and non-estrogenic actions including proliferative and inflammatory properties. Design: We studied 209 EM cases and 115 women without EM. Methods: Pain-related outcomes were assessed using surveys with validated scales. Preoperative serum levels of parent estrogens (estradiol (E2) and estrone (E1)), their 2-, 4- and 16- hydroxylated (OH) and methylated (MeO) derivatives (n=16) were measured by mass spectrometry. We evaluated the associations between estrogen levels and EM anatomic sites, surgical stage, risk of EM, and symptoms reported by women. Spearman correlations established the relationships between circulating steroids. Results: Of the sixteen estrogens profiled, eleven were detected above quantification limits in most individuals. Steroids were positively correlated, besides 2-hydroxy 3MeO-E1 (2OH-3MeO-E1). Higher 2OH-3MeO-E1 was linked to an increased risk of EM (Odd ratio (OR)=1.91 (95%CI 1.09-3.34); P=0.025). Ovarian EM cases displayed enhanced 2-hydroxylation with higher 2MeO-E1 and 2OH-E1 levels (P<0.009). Abdominal, pelvic and back pain symptoms were also linked to higher 2OH-3MeO-E1 levels (OR=1.86; 95%CI 1.06-3.27; P=0.032). Conclusions: The 2-hydroxylation pathway emerges as an unfavorable feature of EM, and is associated with ovarian EM and pain related outcomes.